A study of assessment of infant feeding practices in urban slum of Bhopal, Madhya Pradesh, India - Dr. Astha Tiwari; Dr. Umesh Patel; Dr. Deepti Singh; Dr. Sunita Lakhwani; Dr. Kirti Vishwakarma (Pediatric Review: International Journal of Pediatric Research, 2019)
Background and Objective: Optimal breastfeeding and complementary feeding practices could reduce childhood morbidity and mortality dramatically in most cost-effective and efficacious way. Proper assessment of mothers knowledge regarding feeding practices and identifying the influencing factors that lead to faulty feeding practices is the need of the hour. Breastfeeding is of extreme importance for safeguarding health and welfare of growing infant and this practice must be preserved, protected and promoted by all means. with this background, this study was conducted to assess the infant feeding practices in urban slums and to determine the factors influencing it. Materials and Methods: A community based, cross sectional study conducted in urban slums in Bhopal. Madhya Pradesh for a period of 3 months A predesigned semi structured questionnaire using open and close ended questions were used to collect the information. Results: Out of the 170 mothers enrolled in the study, 53(31.17%) mothers had started feeding within 1 hour of delivery. Prelacteal feed and colostrums was given to82 (48.23%) and 61.76% respectively. Exclusive breastfeeding up to 6 months of age was 88 (51.76%). Significant association was observed between maternal literacy and practice of EBF. and giving prelacteal feeds.51.76% infants started receiving complementary feeding at right time .60(35.29%) breast feeding knowledge and awareness was obtained by health personnel. Conclusion: This study shows that inappropriate feeding practices like giving prelacteals, discarding colostrums, delayed initiation of breastfeeding are prevalent in urban slums. Prevalence of exclusive breast feeding up to 6 months is less than the national level data. Awareness of mothers regarding correct feeding practices should be done at primary health care level.